Peranan Anggaran Belanja Sebagai Salah Satu Alat Perencanaan Dan Pengendalian - Rina Sonia; Purwanti (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
The budget is one of the most important elements and is an influential tool in the company of the company's work program, planning and control. With the budget breakdown, managers or company leaders will find it easier to run and control the work program that has been planned. In order for the budget made to reflect justice so that the implementer does not feel pressured, but motivated, to make a budget realization report an accurate and timely report is needed so that any adverse deviation can be anticipated early. Before preparing a budget, top management first sets out the company's grand plan, such as goals, policies, assumptions as the basis for budgeting.